Struktur keluarga dan perilaku merokok pada remaja: analisis data sakerti 3 tahun 2000 - Isnaini Putri; Mubasysyir Hasanbasri; Djaswadi Dasuki (Berita Kedokteran Masyarakat (BKM), 2004)
Backgrounds: Several conditions such as lung cancer, bronchitis, heart disorder, stroke and reproductive health problems are related to smoking. Number of adolescent smokers are increasing. The Indonesia Smoking Survey 2001 reported that about 40% of adolescents were smokers. We study smoking among adolescents in the context of family social control and health behavior. Parents' social control is important in healthy behavior. The absence of parental control provides a greater chance for adolescents to be influenced by their peer and social environment. Family structure is defined in terms of the living arrangement. We assume that adolescents who live with parents have a close control and social support for positive health behavior. Adolescents who do not live with their parents are assumed to have a weak control than those who do, and therefore they are more likely to smoke. Objectives: This study examines the relationship between not-living with parents (vs living with parents) and smoking status among adolescents. Methods: This study uses the 2000 Indonesian Family Life Survey, with the sample of 10136 respondents aged 15-24 in 13 provinces in Indonesia. If a respondent smokes during the survey, we include them as smoker. Others are non-smokers. The main statistical analysis used in this study is logistic regression. Results: Controlling for age, education, working status, rural-urban, parental smoking, there is a significant relationship between not-living with parents and smoking. Adolescents who did not live with their parents are 3.4 times more likely to smoke than those who did. Conclusion: Living or not living with parents had an impact on adolescent smoking. Some efforts to disseminate information about smoking among adolescents and the stronger regulation on smoking among these age groups are suggested as the substitute for their parental control. Keywords: smoking, adolescents, family structure, SAKERTI 3, living with parents